Survey on Measurement Methods for IPv6 Deployment - Iró, Viktória; Lencse, Gábor (Acta Technica Jaurinensis, 2020)
Nowadays we use Internet Protocol (IP) versions 4 (IPv4) and 6 (IPv6) at the same time. It is very difficult to determine the rate of IPv6 and the state of its deployment exactly. In our survey, paper we present some tools and methods that can be used to estimate the proportion of IPv6. First, we will show some server side methods that mostly use provider-measurable data, so they may not be available to everyone. Next, we introduce various client-side tools that can be used in a much broader context, and then present the use of survey methods. Then we are reviewing some researches, which provide more comprehensive insight into the transition to IPv6 using complex measurement methods. Finally, we compare and categorize the presented metrics based on the availability of data sources and the extent of the measurement duration. We know that there is clearly no best among the various methods. Choosing the right technique depends greatly on the data and tools available to the researcher.